(untitled) (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted for a period of 90 days with twelve crossbred calves to investigate the effect of calf starter on growth performance, feed intake, feed conversion efficiency and economics of feeding. The calves were placed under two groups of six in each and fed with calf starter, CS1 and CS2 to Group I and Group II respectively. The calves were also fed with ad libitum green fodder and whole milk. Significant differences (P>0.01) were observed in mean daily body weight gain, feed conversion efficiency, and dry matter intake per 100 kg body weight between the groups. However, no significant difference was observed in respect of linear body measurements, and intake of whole milk, calf starter and green fodder between the groups. Significant differences (P>0.01) were also observed in total serum protein and blood calcium level while no significant difference was observed in blood glucose level between the groups. The total cost of feed and the cost per kg weight gain were found to be lower in Group II.